IMPLEMENTATION OF SHARIA ECONOMIC PRINCIPLES IN THE DEVELOPMENT OF SUPERIOR PRODUCTS OF DARUL MUKHLASHIN ISLAMIC BOARDING SCHOOL THROUGH THE OPOP PROGRAM IN TEGALSIWALAN PROBOLINGGO - Esa wanda Dewantara; Imanuddin Abil Fida; Fareed Ahmad Obaidy; Eltom Ishaq Osman Musa (International Journal of Multidisciplinary Reseach, 2025)
This study examines the implementation of sharia economic principles in the development of superior products of the Darul Mukhlashin Tegalsiwakan Islamic Boarding School through the One Islamic Boarding School One Product (OPOP) program. Pesantren not only advises as a religious educational institution, but also as an agent of community-based economic empowerment. With a qualitative approach through interviews, observations and analysis of this research document, it is revealed that sharia principles such as justice, transparency, and hatred have been applied in the management of cooperatives and the production of banana chips. This implementation increases the economic independence of Islamic boarding schools. Creating jobs and empowering the surrounding community, especially local farmers and artisans. Challenges such as varied sharia literacy and technological limitations still need to be overcome. The OPOP program emphasizes that the collaboration of students, pesantren, and the community can create a competitive economic ecosystem that is in line with Islamic values, supporting local socio-economic welfare in Probolinggo, especially the Tegalsiwalan area.